ANALISIS PEER TO PEER LENDING DI INDONESIA - Risna Kartika (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
Problems arising from the development of fintech include data security and legal certainty of online-based loans so that it impacts on potential risks to consumers and financial stability and integrity. The purpose of this study is to analyze the development of peer to peer lending in Indonesia, which is reviewed based on relevant institutional regulations and literature studies. This research uses a descriptive method with literature review. The results of this study describe the types of fintech that fall into the dominant category in Indonesia are peer to peer lending, peer to peer lending users by productive age with a percentage of 70%. In October 2019 the number of loans increased 200.01%. The government supervises peer to peer lending through three institutions there are Bank Indonesia, the Ministry of Communication and Information and OJK. The three institutions oversee operations from the start up to consumer protection. Peer to peer lending targets MSMEs that are feasible but cannot obtain bank credit facilities. Peer to peer lending can help develop MSMEs in financial terms, especially in the field of financing.